2007
DOI: 10.1186/1471-2199-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Three novel ABCC5 splice variants in human retina and their role as regulators of ABCC5 gene expression

Abstract: Background: The ABCC5 gene encodes an organic anion pump of the ATP-binding cassette (ABC) transporter family, subclass C. The exact physiological function of ABCC5 however is not known. Here, we have isolated three novel ABCC5 splice variants and characterized their role in the regulation of ABCC5 gene expression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
(36 reference statements)
3
17
1
Order By: Relevance
“…Notably, ABCC5 rs3749438 and rs10937158 are strongly linked (r 2 = 1.0) to respective variants rs3749440 and rs4148575 located in the 3′UTR of an ABCC5 variant transcript (NM_001023587), potentially affecting its expression. This 1933-bp-long truncated ABCC5 transcript variant has been detected previously with at least two-fold greater expression in the distal colon and stomach compared with the full-length ABCC5 transcript and was found to negatively modulate the expression of native ABCC5 mRNA in retinal cells [44]. The change from A to G in rs3749440 induces the creation of a new acceptor splice site, whereas the rs4148575 variation is also located in the 3′UTR of a variant ABCC5 transcript (GenBank AY754874) that undergoes nonsense-mediated decay [44].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Notably, ABCC5 rs3749438 and rs10937158 are strongly linked (r 2 = 1.0) to respective variants rs3749440 and rs4148575 located in the 3′UTR of an ABCC5 variant transcript (NM_001023587), potentially affecting its expression. This 1933-bp-long truncated ABCC5 transcript variant has been detected previously with at least two-fold greater expression in the distal colon and stomach compared with the full-length ABCC5 transcript and was found to negatively modulate the expression of native ABCC5 mRNA in retinal cells [44]. The change from A to G in rs3749440 induces the creation of a new acceptor splice site, whereas the rs4148575 variation is also located in the 3′UTR of a variant ABCC5 transcript (GenBank AY754874) that undergoes nonsense-mediated decay [44].…”
Section: Discussionsupporting
confidence: 58%
“…This 1933-bp-long truncated ABCC5 transcript variant has been detected previously with at least two-fold greater expression in the distal colon and stomach compared with the full-length ABCC5 transcript and was found to negatively modulate the expression of native ABCC5 mRNA in retinal cells [44]. The change from A to G in rs3749440 induces the creation of a new acceptor splice site, whereas the rs4148575 variation is also located in the 3′UTR of a variant ABCC5 transcript (GenBank AY754874) that undergoes nonsense-mediated decay [44]. In a study that included 27 mCRC patients, Di Martino et al [27] found that the ABCC5 marker rs562CC was associated strongly with a 32-fold increase risk of severe diarrhea This specific marker was not significant in our discovery cohort of 167 patients (OR = 1.69, P = 0.297), further reinforcing the need to include a larger number of patients and to replicate findings in an independent cohort.…”
Section: Discussionsupporting
confidence: 58%
“…Expression of MRP5 has been studied only at mRNA level in human material and at protein level in mouse RPE (17,18). We observed MRP4 and MRP5 expression in ARPE-19, D407 and primary human RPE cells at RNA and protein levels ( Figs.…”
Section: Discussionmentioning
confidence: 81%
“…MRP1 protein is present in porcine RPE (1), ARPE-19 cell line, and primary human RPE cells (16). MRP5 was detected recently at the mRNA level in the ARPE-19 cells (17) and human RPE, and at protein level in mouse RPE (18). Several efflux transporters (MRP2, MRP3, MRP4, BCRP) have not been studied in RPE.…”
Section: Introductionmentioning
confidence: 99%
“…However, large-scale computational study demonstrated that as much as one-third of reliable mRNA isoforms (supported by multiple ESTs) may be subject to nonsense-mediated decay and suggest that RUST (regulated unproductive splicing and translation) is one of the major regulatory mechanisms for establishing the right level of gene expression (Lewis at al., 2003). In addition, many minor splice variants are hypothesized to function as dominant negative isoforms that regulate the pathways in which the main functional form is involved (Arinobu et al, 1999; Stojic et al, 2007). …”
Section: Discussionmentioning
confidence: 99%